Prevalence of low-level viremia in people living with HIV/AIDS and its impact on virological failure in Guizhou Province, China - Yan Zheng; Xinling Zha; Hai Long; Wenji Zeng; Junhua Wang; Yongming Yao; Lu Huang; Xiaotian Song; Maosi Wang; Yang Chen; Yang Chen (Frontiers in Public Health)
BackgroundThe frequency of low-level viremia (LLV) may vary across China. This study aims to analyze the epidemiological characteristics and related factors of LLV among HIV/AIDS patients in Guizhou Province from 2016 to 2022, and further analyze the impact of LLV on virological failure (VF).Research design and methodsIn this retrospective cohort study, we analyzed people living with HIV/AIDS whose demographic data, CD4+ T lymphocyte count, and viral load. LLV was defined as at least one VL measurement between 50 and 999 copies/mL after ART. Viral suppression refers to the maintenance of a VL < 50 copies/mL after undergoing ART. VF was defined as a VL ≥ 1,000 copies/mL after ART. To examine and compare the incidence of LLV at different levels, this study divided LLV into three groups based on previous research definitions: low-level LLV (LLLV) ranging from 50 to 199 copies/mL, medium-level LLV (MLLV) ranging from 200 to 399 copies/mL, and high-level LLV (HLLV) ranging from 400 to 999 copies/mL. LLV occurrence frequency was divided into two groups: intermittent LLV (iLLV) was defined as one independent LLV with both the previous and the subsequent viral load below the lower limit of detection. Persistent LLV (pLLV) was defined as at least two consecutive episodes of LLV. We divided the people living with HIV/AIDS into two sub-cohorts based on whether they experienced LLV. Non-LLV was defined as never having experienced LLV. We compared the occurrence of LLV at different levels and frequencies, as well as the risk of virological failure (VF), using the Chi-square test. Non-conditional binary logistic regression analysis was used to identify factors influencing LLV.ResultsIn total, 28,613 cases of infection were analyzed, with 33.72% (9,649/28,613) exhibiting LLV. The LLV proportion rates were 20.69, 6.50, and 6.48% in the low-level LLV (LLLV) (50–199 copies/mL), medium-level LLV (MLLV) (200–399 copies/mL), and high-level LLV (HLLV) (400–999 copies/mL) groups, respectively. The intermittent LLV (iLLV) and persistent LLV (pLLV) groups had LLV rates of 28.65 and 5.07%, respectively. The VF rates were 6.18, 11.79, and 13.70% in the LLLV, MLLV, and HLLV groups, respectively (p < 0.001). The iLLV and pLLV groups had VF rates of 8.82 and 8.14%, respectively (p = 0.397). Multivariate logistic regression analysis revealed that the gender, ethnicity, age at antiretroviral therapy initiation, baseline CD4+ T lymphocyte count, and current treatment regimen were factors influencing the occurrence of LLV.ConclusionThe incidence of LLV among people living with HIV/AIDS treated with INSTI-sparing regimens in Guizhou Province is relatively high and is mainly influenced by factors such as age, CD4+ T lymphocyte count and treatment regimens. A comprehensive assessment of these factors is essential to implement targeted interventions that prevent LLV and enhance the effectiveness of antiretroviral therapy.